2020
DOI: 10.1523/jneurosci.0597-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Stimulation of Type I GAD65+Cells in Taste Buds Activates Gustatory Neurons and Drives Appetitive Licking Behavior in Sodium-Depleted Mice

Abstract: Mammalian taste buds are comprised of specialized neuroepithelial cells that act as sensors for molecules that provide nutrition (e.g., carbohydrates, amino acids, and salts) and those that are potentially harmful (e.g., certain plant compounds and strong acids). Type II and III taste bud cells (TBCs) detect molecules described by humans as "sweet," "bitter," "umami," and "sour." TBCs that detect metallic ions, described by humans as "salty," are undefined. Historically, type I glial-like TBCs have been though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 66 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…Type I cells resemble glia and are the most abundant cells present in taste buds. However, the specific function of type I cells remains elusive 17 , 18 . Some researchers regard type I cells as salt detector 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Type I cells resemble glia and are the most abundant cells present in taste buds. However, the specific function of type I cells remains elusive 17 , 18 . Some researchers regard type I cells as salt detector 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, (Baumer-Harrison et al, 2020) used the same constitutive GAD65Cre mice crossed with floxed ChR2 mice to optogenetically stimulate taste buds. To examine reporter expression in taste buds, they used immunocytochemistry to label Type II (PLCb2) and Type III cells (Car4), and counted cells to determine co-localization with the reporter.…”
Section: Discussionmentioning
confidence: 99%
“…Because they express NTPDase2 for the degradation of ATP released by other cells (Bartel et al, 2006;Vandenbeuch et al, 2013), and because they wrap around Type II and Type III cells (Yang et al, 2020), Type I cells are thought to have a glial-like function, similar to astrocytes in the nervous system. However, several studies have suggested a more complex function of Type I cells including a potential role in amiloride-sensitive salt taste transduction (Vandenbeuch et al, 2008, Baumer-Harrison et al, 2020, release of oxytocin to modulate taste (Sinclair et al, 2010), and release of GABA in response to trigeminal modulation with substance P (Huang and Wu, 2018). In order to examine the potential roles of Type I cells a specific marker is needed to both identify isolated cells for physiology and to manipulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Type II and type III cells express taste receptors and respond to tastants, while type I cells mainly have glial-like functions. Type I cells have also been suggested to be involved in salt transduction because they express amiloride-sensitive Na + channels (Baumer-Harrison et al, 2020;Roper & Chaudhari, 2017;Vandenbeuch et al, 2008;Yang et al, 2020) but a recent study demonstrated that amiloride-sensitive salt taste is transmitted to the nervous system by a unique cell type that expresses the ATP release channel CALHM1/3 and voltage -gated Na + channels, neither of which are found in Type I taste cells (Nomura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 2008 ; Roper & Chaudhari, 2017 ; Baumer‐Harrison et al . 2020 ; Yang et al . 2020 ), but a recent study demonstrated that amiloride‐sensitive salt taste is transmitted to the nervous system by a unique cell type that expresses the ATP release channel CALHM1/3 and voltage‐gated Na + channels, neither of which are found in type I taste cells (Nomura et al .…”
Section: Introductionmentioning
confidence: 99%